ANALISIS FRAUD PENTAGON THEORY DALAM PROSES PENGADAAN BARANG JASA PEMERINTAH: (STUDI EMPIRIS PADA PEMERINTAH DESA DI KECAMATAN SEKARAN) - Lestari, Dwi; Fadjrih Asyik, Nur (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
This study aims to determine the effect of pressure, arrogance, competence, opportunity, and rationalization on the tendency of fraud in the process of government procurement of goods and services. The population of this study were all village officials in Sekaran District, Lamongan Regency. Using the purposive sampling technique, the sample in this study is the primary sample, namely village officials in Sekaran District who have more than 2 years experience in the process of procuring government goods and services with a total of 174 respondents. The data analysis technique used is the Structural Equation Model (SEM) with the Smart application. PLS V4 namely validity test, reliability and hypothesis testing. The results of data processing found that each pressure, arrogance, competence, opportunity, and rationalization had no effect on fraud in the process of procuring government goods and services.